Pengaruh Mental Toughness dan Kecerdasan Emosi terhadap Kecemasan Olahraga pada Atlet Basket SMA Cita Hati Surabaya dalam Menghadapi Event DBL - Oktaviani, Nabila Rahmi; Prihastuti, Prihastuti (EduInovasi: Journal of Basic Educational Studies, 2024)
The purpose of this study was to determine the effect of mental toughness and emotional intelligence on exercise anxiety. This study uses a quantitative approach with an asymmetric regression research design. In this study, a sample of 24 basketball athletes from Cita Hati Surabaya High School was used with a sampling technique, namely purposive sampling. Data analysis used multiple regression analysis techniques anxiety. Multiple regression analysis revealed that F = 1.874 with a significance of 0.178 > 0.05 was not significant. Arinya, you stated that mental toughness and emotional intelligence have no effect on sports anxiety. While partially on the mental toughness variable, the value of t = -1.546 is obtained with a significance of 0.137 > 0.05, not significant. This means that the mental toughness variable partially has no significant effect on the sports anxiety variable. In the emotional intelligence variable, the value of t = -0.888 is obtained with a significance of 0.385 > 0.05, which is not significant. This means that the emotional intelligence variable partially has no significant effect on the sports anxiety variable.